Phosphoric Acid Industry - Problems and Solutions 2017
DOI: 10.5772/intechopen.68658
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends in Phosphatase-Mediated Bioremediation

Abstract: Industrial effluents from tanneries and electroplating industries from small-and large-scale sector industrial plants contain substantial amount of toxic heavy metal, which pollutes rivers and lakes, land, air and sea leading to imbalance of ecosystem and certain health issues to humans, animals as well as plants. The worldwide environmental regulations stipulate the reduction of heavy metals in the effluents to permissible levels before discharging into water bodies. Enzyme-mediated precipitation of heavy met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…According to Mangena [ 32 ], the application of BAP increase the growth parameters of soybean sprouts. This report, together with that of Chaudhuri [ 33 ], emphasized the role of BAP in increasing the plant biomass. Interestingly, the combined physical and chemical priming seemed to enhance the growth parameters in linseed sprouts and reach their highest level, as compared to control and both laser light and BAP treatment separately.…”
Section: Discussionsupporting
confidence: 59%
“…According to Mangena [ 32 ], the application of BAP increase the growth parameters of soybean sprouts. This report, together with that of Chaudhuri [ 33 ], emphasized the role of BAP in increasing the plant biomass. Interestingly, the combined physical and chemical priming seemed to enhance the growth parameters in linseed sprouts and reach their highest level, as compared to control and both laser light and BAP treatment separately.…”
Section: Discussionsupporting
confidence: 59%
“…These results are consistent with those obtained by Behera and others 16 , who reported that the maximum yield of ALP from Alcaligenes faecalis was achieved at 45 °C. The pH of the fermentation broth influences the metabolic activity of microorganisms and thus plays a significant role in the optimization of the fermentation processes; the catalytic activity of ALP has been reported to be regulated mainly by Tris buffers 18 . The obtained results demonstrated that the maximum ALP productivity was recorded at pH values of 9 and 10 (31.7 and 27.19 U L -1 , respectively), with a notable falling off in productivity of ALP for slightly acidic (pH 6.0), neutral (pH 7.0) and slightly alkaline (pH 8.0) conditions to activities of 6.64, 11.46, and 15.76 U L -1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This will be accomplished via the use of cost-effective and sustainable production strategies. Thus, bacterial ALP production in a cost-effective manner, by utilizing bioresources such as biowaste, as well as the effects of the whole bioprocessing process on the environment are two components of sustainable bioprocessing management [ 9 ].…”
Section: Introductionmentioning
confidence: 99%